THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN MEDICINE - Aldanov , Talgat Turdibayevich (Innovative Development in Educational Activities, 2023)
This article delves into the transformative role of Artificial Intelligence (AI) in reshaping healthcare, with a focus on its historical roots, current applications, and future potential. It navigates through the evolution of AI, from its conceptualization in the 1950s to its contemporary applications in medicine, particularly in drug discovery, medical diagnosis, and dentistry. The narrative highlights the challenges and ethical considerations accompanying AI integration in healthcare and emphasizes the collaborative relationship between human expertise and machine precision. The comprehensive exploration of AI’s impact in diverse medical domains underscores its pivotal role in advancing patient care and medical innovation.